Analysis of China’s energy consumption and economic growth based on the Tapio decoupling model - Bai, Xiaohui; Wang, Meng (Frontiers in Climate, 2025)
At present, driven by the urgent demands of the “dual carbon” goals and industrial transformation and upgrading, the underlying logic of the relationship between China’s energy consumption and economic development has undergone changes. This study employs the Tapio decoupling model to analyze the decoupling relationship between China’s energy consumption and economic growth during the period from 2006 to 2024, covering the 11th to the 14th Five-Year Plans, and provides prospects for the 15th Five-Year Plan. The results show that: (1) The decoupling state between China’s total energy consumption and economic growth has shifted from weak decoupling to expansive coupling; however, with the realization of the “dual carbon” goals, the relationship between China’s energy consumption and economic growth is likely to return to the track of weak decoupling during the 15th Five-Year Plan period. (2) Significant differences exist in the decoupling indices among fossil energy sources with different carbon emission levels. Coal and oil generally exhibit a state of weak decoupling, while natural gas has long been in a state of expansive negative decoupling. During the 15th Five-Year Plan period, coal and oil may shift toward strong decoupling, However, natural gas may achieve weak decoupling, as economic growth is becoming increasingly dependent on it. (3) Economic growth shows a high degree of dependence on non-fossil energy, which has long been in a state of expansive negative decoupling, and this state is expected to persist during the 15th Five-Year Plan period. This study helps to explore the internal linkage between energy consumption and economic development, Explore the intrinsic relationship between energy consumption and economic development, along with the underlying reasons for their decoupling state, thus providing references for China’s energy policy optimization, the advancement of the “dual carbon” goals, and industrial transformation.